On surgical failures: onward to objective evaluation of our less proud moments - Henderson, Eric R. (Annals of Joint, 2019)
In recent years a spate of popular writing has focused on the merits of failure (1-6). In various forms, failure is approached from the perspectives of parents (let your children fail!), leaders (allow your employees to fail!), and self-help (let yourself fail and learn from it!). One of my favorite coffee brands states plainly on its container that “things that matter in life” include “never being afraid to fail”. Failure is chic, failure is trending! Twenty years ago, my university commencement speaker orated the experiential virtues of failure as being essential to our growth as individuals and as a society. ‘So, get out there and fail!’ he concluded with gusto. He was not a physician—he taught history.